1999
DOI: 10.1021/bi982295n
|View full text |Cite
|
Sign up to set email alerts
|

Activating Anions That Replace Cl- in the O2-Evolving Complex of Photosystem II Slow the Kinetics of the Terminal Step in Water Oxidation and Destabilize the S2 and S3 States

Abstract: Photosystem II, the multisubunit protein complex that oxidizes water to O2, requires the inorganic cofactors Ca2+ and Cl- to exhibit optimal activity. Chloride can be replaced functionally by a small number of anionic cofactors (Br-, NO3-, NO2-, I-), but among these anions, only Br- is capable of restoring rates of oxygen evolution comparable to those observed with Cl-. UV absorption difference spectroscopy was utilized in the experiments described here as a probe to monitor donor side reactions in photosystem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
109
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(118 citation statements)
references
References 27 publications
(48 reference statements)
8
109
1
Order By: Relevance
“…21 Recent studies have indicated that the presence of Cl is necessary only for the S 2 →S 3 and S 3 →S 0 transitions of the OEC, while the earlier steps of the cycle can proceed in its absence. 48,49 The amplitude and distance changes of Fourier peak III in the S 3 state are less obvious. Peak III appears substantially above the noise level in three of the six S 3 FTs and is readily distinguishable from the noise in two others.…”
Section: Exafs Of the S 3 Statementioning
confidence: 98%
“…21 Recent studies have indicated that the presence of Cl is necessary only for the S 2 →S 3 and S 3 →S 0 transitions of the OEC, while the earlier steps of the cycle can proceed in its absence. 48,49 The amplitude and distance changes of Fourier peak III in the S 3 state are less obvious. Peak III appears substantially above the noise level in three of the six S 3 FTs and is readily distinguishable from the noise in two others.…”
Section: Exafs Of the S 3 Statementioning
confidence: 98%
“…Additionally, it is possible that chloride depletion perturbs a proton exit pathway (37). Such disruption could give rise to long-lived higher S states (38,39) that may increase the probability of the release of partially oxidized water intermediates. These possibilities are not mutually exclusive.…”
Section: Psii Electron Donor Side Ros Production By Incomplete Water mentioning
confidence: 99%
“…The OEC consists of four manganese ions, one calcium ion (3,4,6,7), and probably one chloride ion (Ref . 8, but see also Ref. 9).…”
mentioning
confidence: 92%